Effects of selected soil chemical properties on remediation of Ricinus communis in soil contaminated with sewage sludge - Patek Mohd, Nur Nazirah; Abdu, Arifin; Jusop, Shamshuddin; Abdul Hamid, Hazandy; Karim, Md. Rezaul; Abdul Malik, Mohammad Nazrin; Basri, Mohd Hadi Akbar; Jamaluddin, Aiza Shaliha (Faculty of Computer Science and Information Technology, Universiti Putra Malaysia, 2015)
The increasing of population in Malaysia has led to the increasing of sewage sludge from different area such as domestic and industrial area. Disposing of sewage sludge on cropland is the most economical way because it gives beneficial to the plants. However, it gives a serious impact to the human, plants, animal and environment due to high concentration of heavy metals. Phytoremediation is a green technology that can remove pollutant especially heavy metals from soil contaminated with sewage sludge. Ricinus communis were planted on six different planting media T0 (100% soil-Control), T1 (80% soil + 20% sewage sludge), T2 (60% soil + 40 % sewage sludge), T3 (40% soil + 60% sewage sludge), T4 (20% soil + 80% sewage sludge) and T5 (100% sewage sludge). The results showed that addition of sewage sludge led to increase in pH and also increase in cation exchange capacity (CEC), exchangeable bases (K, Ca and Mg), available phosphorous (available P) and total carbon (TC). All the parameters mentioned above was significantly different with the sewage sludge applied. The highest concentrations of CEC, exchangeable bases (K, Ca and Mg), available P, TC and Mn were observed in treatment T5 (100% sewage sludge). However, Ricinus communis was able to remove Mn effectively from the growth medium. Mn concentration was increased with increasing sewage sludge and decreased after harvesting. Therefore, Ricinus communis was able to taking up Mn as a good phytoextractor.